Availability and utilization of emergency obstetric care public health facilities in Zaria, Northern Nigeria - L., Ya’u Samira; Jamilu, Tukur (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Maternal mortality rates continue to soar high in Northern Nigeria despite all sorts of interventions being put in place. This has necessitated the need to emphasize on Emergency Obstetric Care (EmOC) to tackle obstetric complications which are the largest direct causes of maternal mortality. The study was conducted to assess the availability of Emergency Obstetric Care facilities in Zaria Local Government Area (LGA) located in Northern Nigeria. Methods: This was a hospital based cross- sectional descriptive study carried out in Zaria LGA. Data was collected from seven public health facilities using a structured interviewer administered questionnaire. Results: The LGA met the WHO requirement for the population served while none of the designated BEOC met the UN criteria for such designation. Only 8% of births took place in the health facilities and 0.7% of deliveries were by caesarean section. The met need for EmOC in Zaria LGA was 25.1%. Human resources were lacking in number and skills. Some key drugs and equipment needed to carry out signal function were also absent. Conclusions: Public health facilities in Zaria did not meet the requirements of the United Nations (UN) process indicators. There is need to upgrade the health facilities with the necessary human resource, equipment and facilities to enable them perform their designated EmOC functions.